A continuous fluorescent assay for the determination of plasma and tissue angiotensin I-converting enzyme activity - Alves,M.F. (2005)
A continuous assay using internally quenched fluorescent peptides with the general sequence Abz-peptidyl-(Dnp)P-OH (Abz = ortho-aminobenzoic acid; Dnp = 2,4-dinitrophenyl) was optimized for the measurement of angiotensin I-converting enzyme (ACE) in human plasma and rat tissues. Abz-FRK(Dnp)P-OH, which was cleaved at the Arg-Lys bond by ACE, was used for the enzyme evaluation in human plasma. Enzymatic activity was monitored by continuous recording of the fluorescence (lambdaex = 320 nm and lambdaem = 420 nm) at 37ºC, in 0.1 M Tris-HCl buffer, pH 7.0, with 50 mM NaCl and 10 µM ZnCl2. The assays can be performed directly in the cuvette of the fluorimeter and the hydrolysis followed for 5 to 10 min. ACE measurements in the plasma of 80 healthy patients with Hip-His-Leu and with Abz-FRK(Dnp)P-OH correlated closely (r = 0.90, P < 0.001). The specificity of the assay was demonstrated by the complete inhibition of hydrolysis by 0.5 µM lisinopril or captopril. Abz-FRK(Dnp)P-OH cleavage by ACE was monitored in rat lung, kidney, heart, and liver homogenates in the presence of a cocktail of inhibitors containing trans-epoxy-succinyl-L-leucylamido-(4-guanido)-butene, pepstatin, phenyl-methylsulfonyl fluoride, N-tosyl-L-phenylalanyl-chloromethyl ketone, and N-tosyl-lysyl-chloromethyl ketone to prevent undesirable hydrolysis. ACE activity in lung, heart and kidney homogenates, but not in liver homogenates, was completely abolished by 0.5 µM lisinopril or captopril. The advantages of the method are the procedural simplicity and the high sensitivity providing a rapid assay for ACE determinations.